ANALISIS KEBUTUHAN PENGEMBANGAN PROGRAM PEMBELAJARAN BIOLOGI RAMAH ANAK BERBASIS LINGKUNGAN - Anggi Tias Pratama; Angga Damayanto; Firmansyah Firmansyah; Rizqa Devi Anafiza; Kintan Limiasi; Heru Sukoco (Jurnal Biolokus: Jurnal Penelitian Pendidikan Biologi dan Biologi, 2020)
This study aims to analyze the local potential of Gunung Kidul in developing environmentally friendly child-friendly learning models in learning biology. This research was conducted in Gunung Kidul Regency. The population of this research is all local potential in Gunung Kidul Regency. The sample of this study were high school biology teachers, students' parents, and people with disabilities in Gunung Kidul Regency. Surveys and interviews are carried out through observation as well as some clear information on a study of local potential, biology teachers' perceptions of inclusion, and disability. The data obtained are the local potential in Gunung Kidul and teachers' perceptions about inclusion and persons with disabilities. The results of identification of local potentials owned, namely; Pindul caves, Oya river, Oyot caves, and house buildings which are planted with Tectona grandis and Melaleuca leucadendron trees. The results of interviews with teachers, students' parents, and people with disabilities in Gunung Kidul, so far, learning biology is not yet child-friendly. It has not used the environment as a learning resource. This research concludes that it is necessary to develop an environmentally friendly child-friendly learning model in biology learning.Keywords: Local potential, Child-friendly learning, environment, and biology learning